Why do people seek information about PM2.5 air pollution? A theory of planned behaviour perspective - Amin, Kholidil; Budiarsa, Yohanes Thianika (Jurnal Kajian Komunikasi, 2025)
Background: PM2.5 is a hazardous pollutant that affects human health. Therefore, initiatives to seek information about this air pollution are important so that individuals can be prepared to protect themselves from the dangers of this pollution. Purpose: To examine psychosocial factors in predicting information-seeking intent about PM2.5, and how this intention is related to seeking behaviour regarding PM2.5. Methods: A cross-sectional survey was applied in six provinces on Java Island. A total of 385 respondents were recruited in this study using convenience sampling. PLS-SEM was applied to analyse the collected data and answer the hypotheses. Results: The results reveal that the three psychosocial factors, namely attitude, subjective norms, and perceived behavioural control, significantly affect intention, and subsequently intentions influenced PM2.5 information-seeking behaviour. Another finding also shows that intention can mediate the association between psychosocial factors and information-seeking behaviour. Implication: Theoretical and practical implications are discussed based on the results of this study, including that these findings are useful in the development of health and environmental risk communication, particularly in relation to air pollution in Indonesia. Interventions with a multi-component strategy that addresses attitudes, norms, and perceived control would have the most impact on the development of long-term information-seeking behaviour regarding PM2.5 air pollution.